2017
DOI: 10.1073/pnas.1615233114
|View full text |Cite|
|
Sign up to set email alerts
|

Estrogen receptor α wields treatment-specific enhancers between morphologically similar endometrial tumors

Abstract: The DNA-binding sites of estrogen receptor α (ERα) show great plasticity under the control of hormones and endocrine therapy. Tamoxifen is a widely applied therapy in breast cancer that affects ERα interactions with coregulators and shifts the DNA-binding signature of ERα upon prolonged exposure in breast cancer. Although tamoxifen inhibits the progression of breast cancer, it increases the risk of endometrial cancer in postmenopausal women. We therefore asked whether the DNA-binding signature of ERα differs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…The regulatory proteins used by ESR1 to mediate gene expression in breast cancer cells have been well characterized by multiple laboratories (Carroll et al 2005;Hurtado et al 2011;Magnani et al 2011;Tan et al 2011;Mohammed et al 2013). However, the proteins responsible for mediating these interactions in endometrial cancer have not been established, but ETV4 (Gertz et al 2013) and FOXA1 (Droog et al 2017) have been proposed as key transcription factors. To understand the relationship between mutant ESR1 binding and these factors, we overlapped ESR1 binding sites with the binding sites of FOXA1, which is reported to overlap with 8% of ESR1's binding sites in parental Ishikawa cells, and ETV4, which is reported to overlap with 45% of ESR1's binding sites in parental Ishikawa cells (Gertz et al 2013).…”
Section: D538g Mutation Alters Esr1 Genomic Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory proteins used by ESR1 to mediate gene expression in breast cancer cells have been well characterized by multiple laboratories (Carroll et al 2005;Hurtado et al 2011;Magnani et al 2011;Tan et al 2011;Mohammed et al 2013). However, the proteins responsible for mediating these interactions in endometrial cancer have not been established, but ETV4 (Gertz et al 2013) and FOXA1 (Droog et al 2017) have been proposed as key transcription factors. To understand the relationship between mutant ESR1 binding and these factors, we overlapped ESR1 binding sites with the binding sites of FOXA1, which is reported to overlap with 8% of ESR1's binding sites in parental Ishikawa cells, and ETV4, which is reported to overlap with 45% of ESR1's binding sites in parental Ishikawa cells (Gertz et al 2013).…”
Section: D538g Mutation Alters Esr1 Genomic Bindingmentioning
confidence: 99%
“…Although these studies have uncovered important features of the molecular and phenotypic consequences of ESR1 mutations in breast cancer, similar analyses have not been performed in endometrial cancer cells. Because gene expression responses to estrogens and ESR1 genomic binding are highly dissimilar between breast and endometrial cancer (Gertz et al 2012(Gertz et al , 2013Droog et al 2017), the impact of ESR1 LBD mutations in endometrial cancer cells could be different than the effects observed in breast cancer cells.…”
mentioning
confidence: 99%
“…The use of multiple ESR1 mutant and wildtype clones enabled the discovery of molecular changes that can be reproducibly attributed to the mutation. Wildtype ESR1 binds to different loci in breast cancer and endometrial cancer cells (Gertz et al 2013) and primary tumors (Droog 2017) leading to different transcriptional responses to E2. Mutant ESR1 exhibits a similar cell type-specific pattern in which the genes regulated by mutant ESR1 are different between endometrial cancer cells and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory proteins utilized by ESR1 to mediate gene expression in breast cancer cells have been well characterized by multiple labs (Carroll 2005;Hurtado 2010;Magnani 2011;Tan 2011;Mohammed 2013). However, the proteins responsible for mediating these interactions in endometrial cancer have not been established, but ETV4 (Gertz et al 2013) and FOXA1 (Droog 2017) have been proposed as key transcription factors. To understand the relationship between mutant ESR1 binding and these factors, we overlapped ESR1 binding sites with the binding sites of FOXA1, which is reported to overlap with 8% of ESR1's binding sites in parental Ishikawa cells, and ETV4, which is reported to overlap with 45% of ESR1's binding sites in parental Ishikawa cells (Gertz et al 2013).…”
Section: D538g Mutation Alters Esr1 Genomic Bindingmentioning
confidence: 99%
See 1 more Smart Citation